Faktor-Faktor Pendukung Partisipasi Masyarakat dalam Pembayaran Pajak Bumi dan Bangunan Perdesaan Perkotaan (Pbb P2) di Desa Permisan Kecamatan Jabon Kabupaten Sidoarjo - Andriani, Juwika Prisca; Rodiyah, Isnaini (Journal of Empowerment and Community Service (JECSR), 2023)
This study aims to analyze and describe the factors supporting community participation in the payment of Land and Building Tax (PBB) in Permisan Village, Jabon District, Sidoarjo Regency. This type of research is qualitative research. Data collection techniques were carried out through observation, interviews and documentation. Determination of informants in this study using purposive sampling technique. Data analysis was carried out with data collection techniques, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the factors supporting community participation in paying land and building taxes in Permisan Village are cooperation between officers and groups of Permisan villagers who become pond fisherman laborers to participate by helping submit SPPT to pond owners, the willingness of mandatory officers a tax that collects taxes from residents' homes so that people can know when it is time to pay taxes and the community also does not need to come to the official place of tax payments, the socio-economic conditions of the Permisan village community who have several assets so that it requires a large enough cost to pay taxes, the condition of residence of taxpayers who do not reside in Permisan Village because most of the taxpayers who own ponds are residents from outside Sidoarjo Regency and the low self-awareness of taxpayers in carrying out their obligations is evidenced by the existence of taxpayers who make payments at the end of the year. when there is business or personal interest only.